Discovery-based design of transparent conducting oxide films - Exarhos, Gregory J.; Zhou, Xiao-Dong (Thin solid films, 2007)
The properties of TCO materials derive from the nature, number, and atomic arrangements of metal cations in crystalline or amorphous oxide structures, from the resident morphology, and from the presence of intrinsic or intentionally introduced defects. An enormous body of literature can be accessed from which empirical relationships between structure, composition, charge transport, and transparency have been developed. Previous reviews of this subject have indicated how such information may be used for engineering TCO properties; however, application of more rigorous science-based approaches to the design of materials with superior properties has only recently been tackled. This article summarizes current TCO research results, reviews processing approaches, presents a microscopic description of electronic conductivity in transparent metal oxide systems, and offers guidelines for the design and subsequent development of new materials. The review concludes with a glimpse of some recent work where impedance matching and quantum mechanical tunneling approaches would seem to provide future directions for improving transmissivity in these and similar conducting oxide systems.